Il gomitolo nel folklore: linee per una tipologia - Borghini, Alberto (Studia mythologica Slavica, 1999)
The subject of the research is the ball of thread discussed mainly from its symbolic point of view, which is with the dimension of the hellish, death/murder and witchcraft
Keywords: mitologija; mythology; oral literature; ljudsko slovstvo; Rusija; pravljice